User-centric privacy and security in biometrics - Vielhauer, Claus (The Institution of Engineering and Technology, 2017)
The book reviews developments in the following fields: user-centric privacy; user-centric security; biometrics; digital forensics; and secret-sharing system.
Keywords: Biometric identification.; Computer security.; Data protection.; Privacy.; elektronické knihy; electronic books